Telecommuting, Remote Work, and Hybrid Schedules: Managing the Shift to a Flexible Work Future - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Measures related to the COVID-19 pandemic led state departments of transportation (DOTs) to rapidly expand their flexible work policies and programs. Agencies are continuing to use flexible work arrangements.NCHRP Research Report 1072: Telecommuting, Remote Work, and Hybrid Schedules: Managing the Shift to a Flexible Work Future, from TRB's National Cooperative Highway Research Program, provides successful practices and identifies key considerations to help state DOTs offer flexible work arrangements in an equitable way that sustains agency effectiveness. It also provides guidelines for measuring performance and productivity in ways that do not rely on in-person supervision.Supplemental to the report are a PowerPoint briefing, an implementation memorandum, a set of one-page work-option descriptions, a Flexible Work Arrangement Tracking tool, and a Telework Suitability tool.

Transitions to Alternative Transportation Technologies—Plug-in Hybrid Electric Vehicles - National Research Council (The National Academies Press, 2010)
The nation has compelling reasons to reduce its consumption of oil and emissions of carbon dioxide. Plug-in hybrid electric vehicles (PHEVs) promise to contribute to both goals by allowing some miles to be driven on electricity drawn from the grid, with an internal combustion engine that kicks in when the batteries are discharged. However, while battery technology has made great strides in recent years, batteries are still very expensive. Transitions to Alternative Transportation Technologies–Plug-in Hybrid Electric Vehicles builds on a 2008 National Research Council report on hydrogen fuel cell vehicles. The present volume reviews the current and projected technology status of PHEVs; considers the factors that will affect how rapidly PHEVs could enter the marketplace, including the interface with the electric transmission and distribution system; determines a maximum practical penetration rate for PHEVs consistent with the time frame and factors considered in the 2008 Hydrogen report; and incorporates PHEVs into the models used in the hydrogen study to estimate the costs and impacts on petroleum consumption and carbon dioxide emissions.

Evaluation and Synthesis of Connected Vehicle Communication Technologies - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
In 1999, the Federal Communications Commission (FCC) allocated the intelligent transportation system (ITS) band, also known as the 201c5.9 GHz band,201d for transportation purposes including connected and automated vehicle (CAV) technologies. These technologies enable a host of applications for vehicle2010to-vehicle, vehicle2010to2010infrastructure, and vehicle2010to2010pedestrian communication 2014 collectively known as vehicle2010to2010everything (V2X). Today, the connectivity required for V2X is enabled by dedicated short2010range communications and cellular V2X.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 310: Evaluation and Synthesis of Connected Vehicle Communication Technologies presents a compilation of material on the 5.9 GHz band and the actions taken by the FCC from 2019 through early 2021 to reallocate portions of this band away from dedicated use for traffic flow, traffic safety, and other ITS applications that are essential for CAVs.Supplementary to the document is a video.

The Impacts of Vehicle Automation on the Public Transportation Workforce - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Advancements in the automation of transit vehicles will likely have significant impacts; however, the possible effects on the public-transportation workforce is largely unknown. This is due partly to the fledgling state of transit vehicle automation and partly to the significant amount of uncertainty about how and when automated transit services become more prevalent.The TRB Transit Cooperative Research Program's TCRP Research Report 232: The Impacts of Vehicle Automation on the Public Transportation Workforce provides an analysis of the possible impacts of automation on the public transportation workforce.Supplemental to the report are:00b7 Staffing Count Survey00b7 APTATech Workshop Presentation00b7 Workshop Notes00b7 Employee Survey 00b7 Survey Flyer00b7 Industry Webinar Presentation00b7 Industry Poll Data00b7 Task Impact Ratios, and00b7 Workforce Effect Estimates.

Navigating an Electric Vehicle Future: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The widespread adoption of electric vehicles will play a critical role in decarbonizing the transportation sector as the nation moves toward net-zero emissions. Recent announcements from automakers and the federal government, as well as provisions in the Infrastructure Investment and Jobs Act of 2021, aim to stimulate electric vehicle (EV) deployment, and ongoing technology improvements continue to make EVs a more affordable and practical option. However, many challenges remain to meet the needs of all buyers and drivers and to ensure that manufacturing supply chains and the electric system can support this large-scale transformation. As a follow-up activity to its 2021 report Assessment of Technologies for Improving Light-Duty Vehicle Fuel Economy - 2025-2035, the National Academies of Sciences, Engineering, and Medicine convened a 4-day virtual workshop on October 25-28, 2021, to identify some of the challenges to widespread EV deployment and discuss policy, technical, and market strategies to help federal agencies and other stakeholders plan for the future. This publication summarizes the presentation and discussion of the workshop.

Identifying and Prioritizing Behavioral Interventions to Improve Child Passenger Safety in For-Hire Vehicles - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Child restraint systems (CRS) requirements for children in rideshare vehicles vary by state and city. In 43 states, child passengers in rideshare vehicles are required to be secured in appropriate CRS. However, 28 states exempt taxis from the CRS requirement. Of the 12 cities with relevant policies, eight (67%) require CRS in rideshare vehicles, but not taxis; two cities (17%) require CRS use in both rideshare vehicles and taxis.BTSCRP Research Report 6: Identifying and Prioritizing Behavioral Interventions to Improve Child Passenger Safety in For-Hire Vehicles, from TRB's Behavioral Traffic Safety Cooperative Research Program, provides, in Part I, guidelines for improving child passenger safety in rideshare and taxi vehicles. The guide covers steps to ensure CRS requirements are complete and consistent, strategies for communicating with for-hire companies, and suggestions for legislative provisions. Part II discusses the goals and methods employed for this project2019s research.Supplemental to the report are appendices A-K, a summary of city CRS policies, and a summary of state CRS policies.

Practices for Adding Bicycle and Pedestrian Access on Existing Vehicle Bridges - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Many bridges are built without accommodations for active transportation users and only serve motorized traffic. The pedestrians and bicyclists who rely on these bridges are exposed to safety-related concerns and their access to equal employment opportunities and essential services may be hindered.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 604: Practices for Adding Bicycle and Pedestrian Access on Existing Vehicle Bridges documents the practices employed by state departments of transportation to provide or improve access to existing vehicle bridges for active transportation users.

Guide to Alternative Technologies for Preventing and Mitigating Vehicle Intrusions into Highway Work Zones - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Work zone intrusion technologies are designed to warn workers and drivers of potential intrusion, provide a barrier to prevent intrusion, detect and alert drivers and workers during intrusion, and\/or protect workers and drivers following intrusion.The TRB National Cooperative Highway Research Program's NCHRP Research Report 1003: Guide to Alternative Technologies for Preventing and Mitigating Vehicle Intrusions into Highway Work Zones is designed to be applicable to the construction and maintenance work performed by all departments of transportation and to help reduce motorist and worker injuries and fatalities.Supplemental to the report are NCHRP Web-Only Document 322: Alternative Technologies for Mitigating the Risk of Injuries and Deaths in Work Zones: Conduct of Research, a presentation, an implementation memo, a Decision Support System User Guide Coversheet, a Decision Support System User Guide, and a Decision Support System Tool.

Assessment of Technologies for Improving Light-Duty Vehicle Fuel Economy—2025-2035 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
From daily commutes to cross-country road trips, millions of light-duty vehicles are on the road every day. The transportation sector is one of the United States2019 largest sources of greenhouse gas emissions, and fuel is an important cost for drivers. The period from 2025-2035 could bring the most fundamental transformation in the 100-plus year history of the automobile. Battery electric vehicle costs are likely to fall and reach parity with internal combustion engine vehicles. New generations of fuel cell vehicles will be produced. Connected and automated vehicle technologies will become more common, including likely deployment of some fully automated vehicles. These new categories of vehicles will for the first time assume a major portion of new vehicle sales, while internal combustion engine vehicles with improved powertrain, design, and aerodynamics will continue to be an important part of new vehicle sales and fuel economy improvement. This study is a technical evaluation of the potential for internal combustion engine, hybrid, battery electric, fuel cell, nonpowertrain, and connected and automated vehicle technologies to contribute to efficiency in 2025-2035. In addition to making findings and recommendations related to technology cost and capabilities, Assessment of Technologies for Improving Light-Duty Vehicle Fuel Economy - 2025-2035 considers the impacts of changes in consumer behavior and regulatory regimes.

Reducing Fuel Consumption and Greenhouse Gas Emissions of Medium- and Heavy-Duty Vehicles, Phase Two: Final Report - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine
Medium- and heavy-duty trucks, motor coaches, and transit buses - collectively, \

Assessment of Hybrid-Electric Transit Bus Technology - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2009)
TRB2019s Transit Cooperative Research Program (TCRP) Report 132: Assessment of Hybrid-Electric Transit Bus Technology explores decision-making guidelines coupled with a comprehensive life cycle cost (LCC) model designed to assist transit managers in evaluating, selecting, and implementing hybrid-electric technology options for transit buses. The LCC model allows the user to compare the total life cycle costs across several cost categories for up to 6 different 201cpurchase scenarios.201d The LCC model is contained on the accompanying CD-ROM (CRP-CD-71), with the printed version of the report and available for download as an ISO image online.Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below. Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large and may take some time to download using a high-speed connection. Any software included is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively 201cTRB201d) be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.)

A Look at the Legal Environment for Driverless Vehicles - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Legal Research Digest 69: A Look at the Legal Environment for Driverless Vehicles explores legal policy issues that may be associated with driverless vehicles. It provides an introduction to how civil and criminal liability may adhere to driverless vehicles, the implications of these vehicles for privacy and security, how these vehicles are likely to become subject to and potentially alter prevailing automobile insurance regimes, and other related topics.

Light Rail Vehicle Collisions with Vehicles at Signalized Intersections - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2008)
TRB's Transit Cooperative Research Program (TCRP) Synthesis 79: Light Rail Vehicle Collisions with Vehicles at Signalized Intersections explores mitigation methods tested and used by transit agencies to reduce collisions between light rail vehicles (LRVs) and motor vehicles where light rail transit (LRT) runs through or adjacent to highway intersections controlled by conventional traffic signals.

Distracted Driving Countermeasures for Commercial Vehicles - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2012)
TRB2019s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 24: Distracted Driving Countermeasures for Commercial Vehicles examines driving distractions, as well as any protective (safety-enhancing) effects of particular devices. Distracted driving for commercial drivers is defined as attending to tasks not directly related to operating the vehicle.

Strategies to Advance Automated and Connected Vehicles - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) has released Strategies to Advance Automated and Connected Vehicles: Briefing Document. It is intended for state, regional, and local agency and political decision makers who are framing public policy making for these transformational technologies. The briefing document makes the case for taking action in spite of uncertainties and presents 18 policy and planning strategies that may be useful in advancing societal goals.The briefing document is based on NCHRP Research Report 845: Advancing Automated and Connected Vehicles: Policy and Planning Strategies for State and Local Transportation Agencies. The report assesses policy and planning strategies at the state, regional, and local levels that could influence private-sector automated vehicle (AV) and connected vehicle (CV) choices to positively affect societal goals. The report aims to assist agencies with exploring actions that might increase the likelihood that AV and CV technologies will have beneficial impacts on traffic crashes, congestion, pollution, land development, and mobility (particularly for older adults, youths under the age of 16, and individuals with disabilities).TRB has partnered with the American Association of State Highway and Transportation Officials (AASHTO) to develop a Transportation TV Special Report on Automated Vehicles in America, featuring the results of this briefing document.

Use of Mobility Devices on Paratransit Vehicles and Buses - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2014)
TRB2019s Transit Cooperative Research Program (TCRP) Report 171: Use of Mobility Devices on Paratransit Vehicles and Buses describes the current and emerging issues which limit the use of mobility devices in paratransit vehicles and buses, and includes a guidance document to assist transit systems, manufacturers, and transit users in the implementation of potential accessible design and accommodation solutions for the short and long term.

Assessment of Fuel Economy Technologies for Light-Duty Vehicles - National Research Council (The National Academies Press, 2011)
Various combinations of commercially available technologies could greatly reduce fuel consumption in passenger cars, sport-utility vehicles, minivans, and other light-duty vehicles without compromising vehicle performance or safety. Assessment of Technologies for Improving Light Duty Vehicle Fuel Economy estimates the potential fuel savings and costs to consumers of available technology combinations for three types of engines: spark-ignition gasoline, compression-ignition diesel, and hybrid. According to its estimates, adopting the full combination of improved technologies in medium and large cars and pickup trucks with spark-ignition engines could reduce fuel consumption by 29 percent at an additional cost of 2,200 to the consumer. Replacing spark-ignition engines with diesel engines and components would yield fuel savings of about 37 percent at an added cost of approximately 5,900 per vehicle, and replacing spark-ignition engines with hybrid engines and components would reduce fuel consumption by 43 percent at an increase of 6,000 per vehicle. The book focuses on fuel consumption2014the amount of fuel consumed in a given driving distance2014because energy savings are directly related to the amount of fuel used. In contrast, fuel economy measures how far a vehicle will travel with a gallon of fuel. Because fuel consumption data indicate money saved on fuel purchases and reductions in carbon dioxide emissions, the book finds that vehicle stickers should provide consumers with fuel consumption data in addition to fuel economy information.

Cost, Effectiveness, and Deployment of Fuel Economy Technologies for Light-Duty Vehicles - National Research Council (The National Academies Press, 2015)
The light-duty vehicle fleet is expected to undergo substantial technological changes over the next several decades. New powertrain designs, alternative fuels, advanced materials and significant changes to the vehicle body are being driven by increasingly stringent fuel economy and greenhouse gas emission standards. By the end of the next decade, cars and light-duty trucks will be more fuel efficient, weigh less, emit less air pollutants, have more safety features, and will be more expensive to purchase relative to current vehicles. Though the gasoline-powered spark ignition engine will continue to be the dominant powertrain configuration even through 2030, such vehicles will be equipped with advanced technologies, materials, electronics and controls, and aerodynamics. And by 2030, the deployment of alternative methods to propel and fuel vehicles and alternative modes of transportation, including autonomous vehicles, will be well underway. What are these new technologies - how will they work, and will some technologies be more effective than others? Written to inform The United States Department of Transportation's National Highway Traffic Safety Administration (NHTSA) and Environmental Protection Agency (EPA) Corporate Average Fuel Economy (CAFE) and greenhouse gas (GHG) emission standards, this new report from the National Research Council is a technical evaluation of costs, benefits, and implementation issues of fuel reduction technologies for next-generation light-duty vehicles. Cost, Effectiveness, and Deployment of Fuel Economy Technologies for Light-Duty Vehicles estimates the cost, potential efficiency improvements, and barriers to commercial deployment of technologies that might be employed from 2020 to 2030. This report describes these promising technologies and makes recommendations for their inclusion on the list of technologies applicable for the 2017-2025 CAFE standards.

Overcoming Barriers to Deployment of Plug-in Electric Vehicles - Transportation Research Board; National Research Council (The National Academies Press, 2015)
In the past few years, interest in plug-in electric vehicles (PEVs) has grown. Advances in battery and other technologies, new federal standards for carbon-dioxide emissions and fuel economy, state zero-emission-vehicle requirements, and the current administration's goal of putting millions of alternative-fuel vehicles on the road have all highlighted PEVs as a transportation alternative. Consumers are also beginning to recognize the advantages of PEVs over conventional vehicles, such as lower operating costs, smoother operation, and better acceleration; the ability to fuel up at home; and zero tailpipe emissions when the vehicle operates solely on its battery. There are, however, barriers to PEV deployment, including the vehicle cost, the short all-electric driving range, the long battery charging time, uncertainties about battery life, the few choices of vehicle models, and the need for a charging infrastructure to support PEVs. What should industry do to improve the performance of PEVs and make them more attractive to consumers? At the request of Congress, Overcoming Barriers to Deployment of Plug-in Electric Vehicles identifies barriers to the introduction of electric vehicles and recommends ways to mitigate these barriers. This report examines the characteristics and capabilities of electric vehicle technologies, such as cost, performance, range, safety, and durability, and assesses how these factors might create barriers to widespread deployment. Overcoming Barriers to Deployment of Plug-in Electric Vehicles provides an overview of the current status of PEVs and makes recommendations to spur the industry and increase the attractiveness of this promising technology for consumers. Through consideration of consumer behaviors, tax incentives, business models, incentive programs, and infrastructure needs, this book studies the state of the industry and makes recommendations to further its development and acceptance.

Clean Vehicles, Fuels, and Practices for Airport Private Ground Transportation Providers - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 89: Clean Vehicles, Fuels, and Practices for Airport Private Ground Transportation Providers documents effective approaches and reviews best practices employed by airports to encourage different types of private ground transportation providers to run more environmentally friendly operations. The report summarizes the experiences of public-use airports with developing and implementing clean vehicle policies involving private ground transportation operators serving the airports.Download the report appendices online:Appendix A: Survey Questionnaires Appendix B: List of Survey RespondentsAppendix C: Survey Response SummariesAppendix D: Airport ResourcesAppendix E: Airports' Ground Transportation Mode SplitAppendix F: Fleet and Ownership Model of Ground Transportation (GT) ProvidersAppendix G: Alternative Fuel Vehicles' Emission Comparison